Prevalence of HIV, Syphilis, Hepatitis-B, and Hepatitis-C among People with Injecting Drugs in Western Terai Highway districts, Nepal - paudel, Tarun; Rawal, Bir; Deuba, Keshab; Kakchapati, Sampurna; Amgain, Kapil; Sanjel, Seshananda (Journal of Karnali Academy of Health Sciences, 2019)
Introduction: HIV epidemic has become the major problems among people with injecting drugs (PWIDs) in Nepal. The study was carried out to assess the prevalence of sexually transmitted diseases including HIV/AIDS among PWIDs. Methods: This descriptive cross-sectional survey was conducted in male PWIDs of age more than 16 years residing in Western to Far West Terai Districts of Nepal who had been injecting drugs for three months prior to the date of the survey" March-April 2017. A two-stage cluster sampling was used to recruit 300 PWIDs from seven Districts. HIV was diagnosed by using standard techniques approved by WHO. Similarly, Syphilis was tested using the "Rapid Plasma Reagin" and Hepatitis C as well as Hepatitis B was tested by using rapid test kits. Demographic data were collected by using structured questionnaire and the data obtained were entered in MS excel was transformed into the SPSS version 21 for the descriptive as well as inferential analysis. Results: Prevalence of HIV, HBV, HCV, and STI among PWIDs were 5.3%, 2.7%, 23.7%, and 2.0% respectively. Majority of the PWIDs were literate (93.7%) and their age was below 35 years. Among the married PWIDs, 32.4% had got married before the age of 19. Similarly, 53.7% of them were living with their female sexual partner, and 95.0% were living with their wife. Ninety six percent of the respondents reported to be ever involved in sexual activity, 77.1% of them initiated the sexual intercourse before the age of 20 years and 41.9% of them had more than one female sexual partner. The survey indicated that 36.3% had been injecting drugs for more than 5 years while 27.7% had been injecting for last 2-5 years and 55.0% of the respondents had injected for the first time at the age of 16-24 years. About one in 10 respondents had started injecting drugs recently. Conclusion: There is high prevalence of HIV, HCV, HBV and active syphilis among the PWIDs. Co-infection of HIV and HCV as well as Hepatitis B and C were also prevalent among PWIDs. Comprehensive education and awareness program is required to reduce the prevalence.